Peran Anggota Dewan Perempuan Periode 2019-2024 Dalam Fungsi Legislasi Di DPRD Kabupaten Buton - Hasni, Hasni; La Parasit, La Parasit; La Ode Muhammad, Arsal (Jurnal Sosiologi Miabhari, 2025)
This study aims to analyze the role of female members of the Buton Regency Regional People’s Representative Council (DPRD) for the 2019–2024 period in carrying out their legislative functions, as well as to identify the constraints they encounter. Employing a qualitative approach with purposive sampling techniques, data were collected through in-depth interviews with female council members, male council members, community leaders, and through documentary research. The analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that women’s representation in the Buton Regency DPRD possesses considerable descriptive and symbolic significance, as evidenced by the presence of 24% female members, including a female council chair, which influences public perceptions positively and motivates greater political participation among women. Nevertheless, their substantive contribution to legislative work remains limited, as indicated by the underutilization of the right of initiative to propose gender-responsive local regulations, the low frequency of public dissemination of enacted regulations, and technical constraints such as limited budgetary resources. The primary obstacles include the low proportion of female representation, the dominance of infrastructure-related agendas promoted by male members, and the lack of training and institutional support for gender-responsive legislative capacity. These findings reinforce the view that gender-affirmative policies are insufficient if focused solely on numerical quotas and must be complemented by capacity building, structural support, and political networking. Consequently, the effectiveness of women’s roles in the Buton Regency DPRD will largely depend on the extent to which capacity enhancement and institutional reinforcement can be implemented in future terms—an issue that remains both a challenge and an opportunity for further sociopolitical inquiry.